2011
DOI: 10.1155/2011/314507
|View full text |Cite
|
Sign up to set email alerts
|

Applications of GIS and Very High-Resolution RS Data for Urban Land Use Change Studies in Mongolia

Abstract: The aim of this study is to analyze the urban land use changes occurred in the central part of Ulaanbaatar, the capital city of Mongolia, from 1930 to 2008 with a 10-year interval using geographical information system (GIS) and very high-resolution remote sensing (RS) data sets. As data sources, a large-scale topographic map, panchromatic and multispectral Quickbird images, and TerraSAR synthetic aperture radar (SAR) data are used. The primary urban land use database is developed using the topographic map of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…and 4) the applications of high-resolution panchromatic and multispectral Quickbird images, and TerraSAR synthetic aperture radar (SAR) data are used for urban land use change studies in the central part of Ulaanbaatar, the capital city of Mongolia. Results of the fused image in Ulaanbaatar city show an increased urbanization leading to land use change [14]. [15] fused airborne LiDAR data with aerial images for a tree-level urban forest inventory.…”
Section: Role Of Multisensor Image Fusion In Urban Forest Managementmentioning
confidence: 99%
“…and 4) the applications of high-resolution panchromatic and multispectral Quickbird images, and TerraSAR synthetic aperture radar (SAR) data are used for urban land use change studies in the central part of Ulaanbaatar, the capital city of Mongolia. Results of the fused image in Ulaanbaatar city show an increased urbanization leading to land use change [14]. [15] fused airborne LiDAR data with aerial images for a tree-level urban forest inventory.…”
Section: Role Of Multisensor Image Fusion In Urban Forest Managementmentioning
confidence: 99%
“…With respect to land use, the city has undergone a dramatic urbanization trend during the last decade (the urban land use distribution of Ulaanbaatar city is presented in Table 1). Using high-resolution satellite image fusion interpretation, Amarsaikhan et al [18] concluded that the central part of Ulaanbaatar city was urbanized very rapidly. In the socialist time, 1930-1990, 571 buildings were constructed, while during the first years of post-socialist time, 1990-2008, 792 buildings were raised, which demonstrates a significant land demand for urban development.…”
Section: Study Areamentioning
confidence: 99%
“…While the term informal settlement is understood in Mongolia (Radnaabazar et al ., 2004), it is generally absent from studies and policies exploring urban growth. Rather, most scholars and policy documents simply use the term ger district (or ger area) instead of informal settlements (Amarsaikhan et al ., 2007, 2009; Suvdantsetseg, 2008). This is an important discursive position as the ger districts of Ulaanbaatar fail to meet many of the criteria used for informal settlements, and indeed, are seen to offer a socially accepted development form.…”
Section: Ger Districts As Informal Settlementsmentioning
confidence: 99%
“…Importantly, ger districts represent the primary housing location for new residents migrating to the city from rural areas, with 73% of those settled in these areas lacking the correct permissions (MSWL and UNDP, 2009). Amarsaikhan et al . (2009: 13) point out that ger districts in Ulaanbaatar grew by 58% between 1990 and 2001.…”
Section: Introductionmentioning
confidence: 99%